Evolutionary interactions between thermal ecology and sexual selection. (13th July 2022) - Leith, Noah T.; Fowler‐Finn, Kasey D.; Moore, Michael P.
Abstract: Thermal ecology and mate competition are both pervasive features of ecological adaptation. A surge of recent work has uncovered the diversity of ways in which temperature affects mating interactions and sexual selection. However, the potential for thermal biology and reproductive ecology to evolve together as organisms adapt to their thermal environment has been underappreciated. Here, we develop a series of hypotheses regarding (1) not only how thermal ecology affects mating system dynamics, but also how mating dynamics can generate selection on thermal traits; and (2) how the thermal consequences of mate competition favour the reciprocal co‐adaptation of thermal biology and sexual traits. We discuss our hypotheses in the context of both pre‐copulatory and post‐copulatory processes. We also call for future work integrating experimental and phylogenetic comparative approaches to understand evolutionary feedbacks between thermal ecology and sexual selection. Overall, studying reciprocal feedbacks between thermal ecology and sexual selection may be necessary to understand how organisms have adapted to the environments of the past and could persist in the environments of the future. Abstract : Reciprocal interactions between thermal ecology and sexual selection may be pervasive features of adaptation. We hypothesize (1) how thermal ecology affects and is shaped by mating system dynamics; and (2) how the thermal consequences of mate competition favor the co‐adaptation of thermal biology and sexual traits. Studying these evolutionary feedbacks may be necessary to understand how organisms have adapted to the environments of the past and could persist in the environments of the future.